Acting in Isolation: Safeguarding and anti-trafficking officers' evidence and intelligence practices at the border - Lynch, Jennifer K.; Hadjimatheou, Katerina (Anti-Trafficking Review, 2017)
Internationally, the border has been presented as a site of unique opportunity for the identification and protection of victims of human trafficking. In the UK, the establishment of specialist safeguarding and anti-trafficking (SAT) units within the border force has raised questions about the challenges for border force officers (BFOs) of balancing the enforcement of strict immigration rules with the protection of victims under anti-trafficking legislation. In this paper we draw on data collected from a study of anti-trafficking initiatives at Heathrow airport to consider a particular area of BFO frustration with SAT work: the collection and use of evidence and intelligence to support investigation and pursuit of potential SAT cases at the border. Our findings focus on the use of intelligence and data to inform initiatives and develop a comprehensive understanding of the trafficking problem; and the scope of BFO powers of evidence-collection on the frontline. The experience of BFOs points to a team often working in isolation as they attempt to traverse gaps in data collection and limits to their powers to gather evidence in pursuit of their duty to identify victims of trafficking at the UK border. We conclude by making proposals for how the border force and central government could improve evidence and intelligence practices in ways that translate into both more coherent anti-trafficking policy and better identification and support for victims.